PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TREFFINGER TERHADAP PEMAHAMAN SISWA PADA MATERI NORMA DALAM KEIDUPANKU KELAS V SD NEGERI 6 PANGKALPINANG - Nashwa Syafa Kamila; Diana Pramesti; Said Akhmad Maulana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low level of students' understanding, as evident from the results of a comprehension test, in which 28 out of 32 students scored below the minimum passing grade of 70. This study aimed to determine the effect of the Treffinger-type cooperative learning model on students' understanding of the Norms in My Life material in fifth grade at SD Negeri 6 Pangkalpinang.The study employed a quantitative experimental approach using a quasi-experimental design with a nonequivalent control group design. The sample consisted of 35 students in the experimental class and 34 students in the control class, selected through purposive sampling. The research instrument was a test comprising 10 essay questions Data analysis techniques included the normality test (Kolmogorov-Smirnov), homogeneity test (Levene's test), and hypothesis testing (independent sample t-test).The results of the normality and homogeneity tests indicated that the data were normally distributed and the two variances were homogeneous. Furthermore, hypothesis testing using the independent sample t-test produced a significance value of 0.000 < 0.05. Thus, Ha was accepted and Ho was rejected, indicating that the Treffinger-type cooperative learning model significantly affected students' understanding of the Norms in My Life material in fifth grade at SD Negeri 6 Pangkalpinang